2013
DOI: 10.4028/www.scientific.net/amr.667.160
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicity of Magnesium Oxide on Human Neuroblastoma SH-SY5Y Cell Lines

Abstract: The use of magnesium oxide (MgO) nanoparticles in industrial applications has been raised over the last decade. However, there is limited toxicology information available regarding the effects of MgO nanoparticles. In this study, cytotoxicity and neurotoxicity of this nanoparticle on SH-SY5Y cell lines was investigated. In order to assess the cytotoxicity effect, SH-SY5Y cells were exposed to three different types of MgO nanoparticles (MgO 5, MgO 10 and MgO 24) for 24, 48 and 72 h. The concentration of nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…About MgO NPs, in that respect are some articles, which have indicated toxic properties[ 22 34 ] and also other articles, which have exhibited the positive effects of MgO NPs on different organisms by changing the concentration and size of MgO NPs. [ 18 23 35 ] Hence, in this work we prospected increasing maintenance of the human lymphocytes by testing different concentrations of MgO NPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About MgO NPs, in that respect are some articles, which have indicated toxic properties[ 22 34 ] and also other articles, which have exhibited the positive effects of MgO NPs on different organisms by changing the concentration and size of MgO NPs. [ 18 23 35 ] Hence, in this work we prospected increasing maintenance of the human lymphocytes by testing different concentrations of MgO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium oxide nanoparticle (MgO NP) is one of the metal oxide NPs, which is extensively used in several industries such as pharmaceuticals, cosmetics, food packaging, electrical insulation, desiccant, and medicine. [ 18 ] It has the advantage of nontoxic, high thermal stability, biocompatible, low cost, and has considerable potential as an antibacterial agent. [ 19 ] A number of studies have also been performed on MgO NPs and have evaluated different mechanistic endpoints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applications of MgO nanoparticles and also the issues on its feasible toxicity are increasing (16). Unfortunately, there is a paucity of knowledge about the effect of the prolonged exposure to nanoparticles on human health and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cytotoxicity and neurotoxicity of MgO nanoparticles on SH-SY5Y cell line have also been investigated, and the results showed that MgO nanoparticles are not toxic in concentration ranges from 1nM to 1mM for 24, 48, and 72 h to both undifferentiated and differentiated SH-SY5Y cells. MTS method was used for cell viability (16).…”
Section: Introductionmentioning
confidence: 99%